A small molecule inhibitor of signal peptide peptidase inhibits Plasmodium development in the liver and decreases malaria severity. - Iana Parvanova; Sabrina Epiphanio; Abdul Fauq; Todd E Golde; Miguel Prudêncio; Maria M Mota (PLoS ONE, 2009)
The liver stage of Plasmodium's life cycle is the first, obligatory step in malaria infection. Decreasing the hepatic burden of Plasmodium infection decreases the severity of disease and constitutes a promising strategy for malaria prophylaxis. The efficacy of the gamma-secretase and signal peptide peptidase inhibitor LY411,575 in targeting Plasmodium liver stages was evaluated both in human hepatoma cell lines and in mouse primary hepatocytes. LY411,575 was found to prevent Plasmodium's normal development in the liver, with an IC(50) of approximately 80 nM, without affecting hepatocyte invasion by the parasite. In vivo results with a rodent model of malaria showed that LY411,575 decreases the parasite load in the liver and increases by 55% the resistance of mice to cerebral malaria, one of the most severe malaria-associated syndromes. Our data show that LY411,575 does not exert its effect via the Notch signaling pathway suggesting that it may interfere with Plasmodium development through an inhibition of the parasite's signal peptide peptidase. We therefore propose that selective signal peptide peptidase inhibitors could be potentially used for preventive treatment of malaria in humans.